Engaging Appalachia : a guidebook for building capacity and sustainability - Fletcher, Rebecca Adkins; Long, Rebecca-Eli; Schumann, William R. (Place matters (Series) (Lexington, Ky.), 2023)
"Inclusive campus-community collaborations provide critical opportunities to build community capacity-defined as a community's ability to jointly respond to challenges and opportunities-and sustainability. Through case studies from across all three subregions of Appalachia from Georgia to Pennsylvania, Engaging Appalachia: A Guidebook for Building Capacity and Sustainability offers diverse perspectives and guidance for promoting social change through campus-community relationships from faculty, community members, and student contributors. This volume explores strategies for creating more inclusive and sustainable partnerships through the arts, humanities, social sciences, and natural sciences. In representing diverse areas, environments, and issues, three relatable themes emerge within a practice viewpoint that is scalable to communities beyond Appalachia: fostering student leadership, asset-building, and needs fulfillment within community engagement. Engaging Appalachia presents collaborative approaches to regional community engagement and offers important lessons in place-based methods for achieving sustainable and just development. Written with practicality in mind, this guidebook embraces hard-earned experiences from decades of work in Appalachia and sets forth new models for building community resilience in a changing world"--